Purification of nucleocapsid protein of Newcastle Disease virus for immunodiagnostic kit - Ahmad Raus, Raha; Awang, Rus Anida; Mel, Maizirwan; Yusoff, K. (IIUM Press, 2011)
The aim of the present study is to purify recombinant nucleocapsid (NP) protein of Newcastle disease virus (NDV) using microfitration fitration system and improve the processing conditions as well. A microporous membrane screening using two different sizes of membrane which are 0.1µm and 0.45µm was performed before further improvement on NP protein filtration was carried out. Several conditions of the independent variables that affect the microfiltration process such as the temperature, transmembrane pressure (TMP), and viscosity were observed. It turned out to be that 0.45µm membrane gave higher yield of NP protein than that of 0.1µm membrane. Thus, 0.45µm membrane was used to improve the filtration process for NP protein. Based on the Full Factorial Design (STATISTICA 8.0, Statsoft, Inc.), eight sets of experiment were designed to identify the best conditions for the NP protein filtration. From these experiments, the optimal conditions that gave the highest yield of NP protein are; TMP 4.5psi, viscosity 2.39cP at 4ºC. Based on ANOVA (analysis of variance), all the independent variables studied do not significantly affect the purification of NP protein. However, based on the lowest p value for each variable corresponding to the response, temperature has the largest effect for the NP protein yield.